On the Natal Philopatry of the Eastern Imperial Eagle of the Volga Population - Mikhail V. Korepov (Пернатые хищники и их охрана)
Population structure across the range of the Eastern Imperial Eagle (Aquila heliaca) remains one of the controversial issues that can be resolved by data on the distribution of juveniles from different points in the range. However, the long period of puberty, the difficulty of establishing a new nesting site in conditions of limited food resources and nesting habitats, the high mortality of juveniles and the short lifespan of tracking devices make this task very difficult. In this respect, any reliable data on the natal philopatry of the Imperial Eagle is of great interest. We have been tagging eagles in the Ulyanovsk Region since 2017.